2009
DOI: 10.1590/s1984-82502009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Responsible self-medication: review of the process of pharmaceutical attendance

Abstract: This article presents a review, based on a qualitative study, of pharmaceutical orientation in the management of minor illness. Action research methodology was used by a group of faculty members responsible for the community pharmacy internship and by postgraduates in clinical pharmacy, to carry out the study with the objective to present a standard service for this kind of procedure. The interaction with the individual starts with a welcoming reception, at which point the pharmacist should be receptive and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 10 publications
2
45
0
11
Order By: Relevance
“…There are several sources for self-medication: sharing of prescription with members of the family or social circle, reusing leftovers, use of previous prescriptions etc. Furthermore, the large product offering, the attraction provided by fads, intense marketing of pharmaceutical industry and even cultural aspects also contribute for this situation [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…There are several sources for self-medication: sharing of prescription with members of the family or social circle, reusing leftovers, use of previous prescriptions etc. Furthermore, the large product offering, the attraction provided by fads, intense marketing of pharmaceutical industry and even cultural aspects also contribute for this situation [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…This has a mean score of 3. Hence, an aggregate mean score above 3 points indicates that the respondents agreed with the statement, while an aggregate mean score below 3 indicates a disagreement with the statement [11]. Therefore, remarks revealed the overall opinion of the respondents as either as "Agreed" or "Disagreed" [11].…”
Section: Data Collectionmentioning
confidence: 99%
“…A review study [10], observed that 50-75% of treatment in the United States and Britain were through selfmedication. Consumers' depth knowledge on drug information and accurate recognition of symptoms of illness, personal medical history, indication and contraindications are some of the variables needed for responsible selfmedication [11]. Nonetheless, drug resistance, drug-induced disease, bacterial infection, hypersensitivity, drug withdrawal syndrome, and even death are occurrences that can result from inappropriate use of self-medication [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in some developing and economically poor countries. However, it was found to be related to socio-economic factors, availability of medications, law, advertisement and lifestyle [2].…”
Section: Introductionmentioning
confidence: 98%